Falling [large type] : a novel - Newman, T. J. (Blackstone Publishing, 2021)
"You just boarded a flight to New York. There are one hundred and forty-three other passengers onboard. What you don't know is that thirty minutes before the flight your pilot's family was kidnapped. For his family to live, everyone on your plane must die. The only way the family will survive is if the pilot follows his orders and crashes the plane. Enjoy the flight." --